Quality of life in sarcopenia measured with the SarQoL questionnaire: A meta-analysis of individual patient data - Beaudart, Charlotte; Tilquin, Noémie; Abramowicz, Pawel; Baptista, Fátima; Peng, Dao Juan; de Souza Orlandi, Fabiana; Drey, Michael; Dzhus, Marta; Fábrega-Cuadros, Raquel; Fernandez-Garrido, Julio; Laurindo, Lucas Fornari; Gasparik, Andrea-Ildiko; et al. (Maturitas, 2024)
Age-related sarcopenia, resulting from a gradual loss in skeletal muscle mass and strength, is pivotal to the increased prevalence of functional limitation among the older adult community. The purpose of this meta-analysis of individual patient data is to investigate the difference in health-related quality of life between sarcopenic individuals and those without the condition using the Sarcopenia Quality of Life (SarQoL) questionnaire. A protocol was published on PROSPERO. Multiple databases and the grey literature were searched until March 2023 for studies reporting quality of life assessed with the SarQoL for patients with and without sarcopenia. Two researchers conducted the systematic review independently. A two-stage meta-analysis was performed. First, crude (mean difference) and adjusted (beta coefficient) effect sizes were calculated within each database; then, a random effect meta-analysis was applied to pool them. Heterogeneity was measured using the Q-test and I2 value. Subgroup analyses were performed to investigate the source of potential heterogeneity. The strength of evidence of this association was assessed using GRADE. From the 413 studies identified, 32 were eventually included, of which 10 were unpublished data studies. Sarcopenic participants displayed significantly reduced health-related quality of life compared with non-sarcopenic individuals (mean difference = -12.32; 95 % CI = [-15.27; -9.37]). The model revealed significant heterogeneity. Subgroup analyses revealed a substantial impact of regions, clinical settings, and diagnostic criteria on the difference in health-related quality of life between sarcopenic and non-sarcopenic individuals. The level of evidence was moderate. This meta-analysis of individual patient data suggested that sarcopenia is associated with lower health-related quality of life measured with SarQoL.
Keywords: průzkumy a dotazníky; Quality of Life; Surveys and Questionnaires; Aged; Prevalence; Sarcopenia; Humans; senioři; lidé; kvalita života; sarkopenie; prevalence